Unveiling the Bioactive Potential of Mannich Bases: Synthesis, Characterization, and Biological Perspectives - Triveni, Singirisetty; Kumar, Yapuri Ashok; Mallela, Vijaya Jyothi; Sai, Gangadhar Gari Ganesh; Vedavathi, Nukala; Rajeshwari, Vishwanadhapalli Raja; Janardhana, Varikuti; Babu, Chilamakuru Naresh (Indian Journal of Pharmaceutical Education and Research)
Background: This study evaluates the antimicrobial and molecular docking profiles of 12 novel Mannich bases (MB1-MB12) to find potential candidates effective against Escherichia coli, Staphylococcus aureus, and Candida albicans. This study discusses the urgent need for new therapeutic agents with enhanced efficacy to combat the fast-growing problem of antimicrobial resistance. The compounds were synthesized using the Mannich reaction, which includes the reaction of aromatic amines, formaldehyde, and aromatic aldehydes under reflux conditions. Materials and Methods: Molecular docking on 2B35 and 4P8O protein targets determined binding affinity, interactions, and energy scores. Analytically, the compounds were characterized and appraised for synthetic feasibility and drug-likeness using ADME predictions and Lipinski's rule of five. MIC testing assessed antimicrobial effectiveness. To assess their therapeutic potential, the compounds' drug-likeness, GI absorption, and synthetic accessibility were examined. Results: The best docking compounds were MB7, MB3, and MB2, which had great binding affinities and significant interactions with key 2B35 residues. MB7 showed stronger antibacterial activity against E. coli (12.5 μg/mL), S. aureus (6.25 μg/mL), and C. albicans. Antifungal activity of MB3 and MB5 was substantial, with MIC values of 1.6 μg/mL against C. albicans. Antibacterial activity was higher in compounds with balanced physicochemical properties such moderate Log P values, hydrogen bonding, and high GI absorption. Conclusion: MB7 emerged as the most promising candidate, demonstrating robust docking and antibacterial activity against bacterial and fungal infections. MB3 and MB5 also showed promise as antifungal agents. These findings emphasize the compounds' potential as leads for further preclinical and mechanistic investigations to tackle drug-resistant illnesses.
Keywords: Mannich bases; Molecular docking studies; ADME prediction; Antitubercular activity; Anti-microbial activity.